Stress proteins in the cytoplasmic membrane fraction of Bacillus subtilis - Petráčková, Denisa; Šemberová, Lenka; Halada, Petr; Svoboda, Petr; Svobodová, Jaroslava (Folia microbiologica, 2010)
Stress proteomes of the cytoplasmic membrane fraction of Bacillus subtilis trp (C2)-exposed to acid pH and ethanol were characterized. Although these stress factors impair the cell function in a specific manner, they share the ability to denature proteins. Therefore, specific and general stress proteins in the membranes were investigated. Both ethanol (3 %) and pH 5.0 increase the doubling time from 17 to 25 min. Isolated cytoplasmic membranes were subjected to an optimized 2D PAGE analysis which permitted the separation and analysis of ?450 distinct protein spots. Two alternative methods of protein detection were compared, i.e. silver staining and (35)S-L-methionine pulse labeling; the stress induced proteins were identified by MALDI-TOF MS. After ethanol stress, five proteins were increased, viz. YdaP, Ctc, YfhM, YjcH and YwaC. Acid stress proteins were AcoB, YkwC, SodA, YjcH and YwaC. Proteins YjcH and YwaC were increased after ethanol as well as acid pH treatment.
Keywords: bakteriální proteiny; Ethanol; buněčná membrána; Methionine; Financing, Organized; regulace genové exprese u bakterií; reakce na tepelný šok; financování organizované; Heat-Shock Response; koncentrace vodíkových iontů; 2D gelová elektroforéza; methionin; Cell Membrane; ethanol; Electrophoresis, Gel, Two-Dimensional; Bacillus subtilis; Bacterial Proteins; proteom; Proteome; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Heat-Shock Proteins; proteiny teplotního šoku; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Gene Expression Regulation, Bacterial; Hydrogen-Ion Concentration